Pengalaman Pemeriksaan IVA pada Perempuan di Jakarta: Studi Fenomenologi - Alexandra Maria Cornelia Sada Ule; Regina Vidya Trias Novita (Lembaga Penelitian dan Pengabdian Masyarakat Politeknik Muhammadiyah Makassar, 2026)
Cervical cancer is a major health problem in Indonesia and globally, with significant incidence and mortality rates. Early detection through Visual Inspection with Acetic Acid (VIA) examination is a crucial step in cervical cancer prevention and control. However, many Women of Childbearing Age (WUS) still hold negative perceptions and face obstacles in undergoing VIA examinations. This study aims to explore the experiences of WUS who have undergone VIA examinations and identify the factors influencing their decisions. This research employs a descriptive phenomenological approach to understand the experiences of WUS in depth. Eight informants, patients at Puskesmas Kembangan, West Jakarta, were interviewed in detail to gather data. The results of the study found 5 major themes, namely the WUS's response during the examination, how to overcome discomfort during the examination, the purpose of the VIA examination, factors influencing the decision to undergo VIA examination, and reproductive health promotion. This study has received ethical approval from the STIK Sint Carolus Institution. Data collection was conducted through in-depth interviews from July 2024 to March 2025. The findings of this study are expected to contribute to efforts to increase WUS participation in early detection of cervical cancer.